Multi-Objective Optimal Design of Water Distribution Networks Accounting for Transient Impacts - Huang, Yuan; Zheng, Feifei; Duan, Huan-Feng; Zhang, Qingzhou (Water resources management, 2020)
Transients are commonly triggered in urban water distribution networks (WDNs) due to daily system management and operation. While these transients are unlikely to cause catastrophic consequences immediately, frequent occurrences can result in prolonged deterioration of infrastructure safety and life cycles in the long term. To account for such impacts in the design of WDNs, a multi-objective optimization method coupled with the Non-dominated Sorting Genetic Algorithm III is proposed in this paper, where two transient-based objectives are incorporated into the WDN design process. Additionally, an engineering design constraint in the decision space is developed to ensure that the sizes of upstream pipes are not smaller than those downstream, thereby improving the engineering practicality of the optimal design solutions. Two WDN cases with transient conditions triggered by pump switching are applied to demonstrate the effectiveness of the proposed method. The results show that the widely used reliability metric based on steady-state conditions is unable to fully represent the transient impacts and that upsizing pipes can reduce transient impacts but at the expense of high economic costs. It is also found that optimally designed pipe diameters can be effective to mitigate transient impacts, in addition to the use of traditional protection devices. The proposed method represents the first step in investigating the underlying relationships between WDN design and unsteady flow effects and is a supplement to current WDN design criteria.